Midazolam-Induced Parasomnia as Online-Shopping Behaviors. Issue 6 (November 2021) - Wang, Chih-Chun; Chen, Tien-Yu; Wan, Fang-Jung; Huang, Yu-Chieh; Tzeng, Nian-Sheng
Abstract : Objectives: The objective of this study was to report a case of sleep online shopping. Methods: A single case study of midazolam-induced sleep online shopping behavior in a 35-year-old woman with posttraumatic stress disorder and bipolar II disorder was performed. Results: The Naranjo score was 7, which supported the probability of midazolam-induced sleep online shopping behaviors. Conclusions: To the best of our knowledge, this is the first case report of parasomnia as online-shopping behaviors, induced by midazolam, in a patient with posttraumatic stress disorder and bipolar disorder. This case could serve as a reminder for the clinicians prescribing midazolam as a hypnotic for insomnia for their patients.